The Potential of Bioactive Peptides from Trypsin-Hydrolyzed Egg White of IPB-D1 Chicken as Antioxidant and Antibacterial - Nova Aryanti; Zakiah Wulandari; Cahyo Budiman (Institut Pertanian Bogor, 2025)
The IPB-D1 chicken is the outcome of crossbreeding native Indonesian chickens and can produce eggs high in protein, which is excellent for bioactive peptide manufacturing. Egg white hydrolysates contain bioactive peptides with antioxidant and antibacterial properties. The purpose of this work was to assess the antioxidant and antibacterial properties of bioactive peptides produced from IPB-D1 egg white hydrolyzed with trypsin. The research procedures included determining the Haugh unit (HU) value, protein content, degree of hydrolysis (DH), and antioxidant and antibacterial activity. The hydrolysate inhibited DPPH by 44.82% and had an antioxidant capacity of 23.16 mg EVC 100/g. The hydrolysate had greater inhibition zones against Gram-positive and Gram-negative bacteria than the non-hydrolyzed egg white, indicating its antibacterial action. Inhibition zone sizes ranged from 2.42 to 3.48 mm. The findings show that enzymatic hydrolysis of IPB-D1 egg white with trypsin significantly improves its antioxidant and antibacterial properties. Keywords: antibacterial, antioxidant, bioactive peptide, IPB-D1 chicken, trypsin enzyme